Lateral wedge insole for knee osteoarthritis: randomized clinical trial - Campos, Gustavo Constantino de; Rezende, Marcia Uchôa; Pasqualin, Thiago; Frucchi, Renato; Bolliger Neto, Raul (São Paulo Medical Journal, 2015)
CONTEXT AND OBJECTIVE: Optimal management of knee osteoarthritis requires a combination of pharmacological and non-pharmacological methods. The use of lateral wedge insoles to treat medial knee osteoarthritis is recommended, but there is still controversy about its efficacy. The purpose of this study was to ascertain whether the use of lateral wedge insoles can diminish pain and improve function in patients with medial knee osteoarthritis. DESIGN AND SETTING: Prospective randomized trial conducted in a tertiary-level hospital. METHODS: We prospectively enrolled 58 patients with medial knee osteoarthritis and randomized them to use either a lateral wedge insole with subtalar strapping (Group W), or a neutral insole with subtalar strapping (Group N - control). All the patients were instructed to use the insole for five to ten hours per day. A visual analogue pain scale, the Western Ontario and McMaster Universities Arthritis Index (WOMAC) and the Lequesne questionnaire were applied at baseline and at weeks 2, 8 and 24. RESULTS: At weeks 8 and 24, both groups showed lower scores for WOMAC (P = 0,023 and P = 0,012 respectively). There were no statistically significant differences between the groups regarding the visual analogue pain scale, WOMAC or Lequesne results at any time evaluated. CONCLUSION: The use of a lateral wedge insole with subtalar strapping improved the patients’ symptoms and function but was not superior to placebo insoles. CLINICAL TRIAL REGISTRATION: NCT01739296.